Laboratory biomarkers of COVID-19 outcome: findings from a high dependency unit of South Bengal - Maji, Rabilochan; Bhattacharjee, Arindam; Elango, Akshaya; Ghosh, Sayan; Gantait, Kripasindhu (International Journal of Research in Medical Sciences, 2021)
Background: Coronavirus disease-19 (COVID-19) has become a world wellbeing compromise. The danger factors for unfavorable occasions of coronavirus disease-19 (COVID-19) have not been very much depicted. This study aimed to explore clinical characteristics, laboratory results, and CT imaging characteristics of COVID-19 patients in Midnapore medical college and hospital and provide evidence for the prevention and treatment of COVID-19. Methods: In this retrospective, single-center study, data of all confirmed patients with COVID-19 admitted at SARI HDU of Midnapore medical college and hospital from 1st July to 21July 2021 were collected and analyzed. Data including clinical presentations, basic laboratory investigations, and CT severity scores were analyzed and compared between survival and death patients. Results: In this study total of 81 patients of COVID-19 admitted at SARI HDU were included (male=50, female=31). The patients were divided into 2 groups according to the outcome: survival group (n=38) and death group (n=43). Information on the overall clinical characteristics of the patients was collected, including age, sexual orientation, past medical history, clinical symptoms, and so on. Compared with the patients in the Survival group, the patients in the death group, the proportion of patients presented with Dyspnoea and suffering from Diabetes and hypertension were higher (p<0.05). In patients of the death group, TLC, CRP, D-dimer, urea, and creatinine had higher values, while the levels of albumin were significantly reduced, and the differences were statistically significant (p<0.05). Between the Survival group and death group, there was no significant difference in other indexes such as NLR, platelet count, and liver enzymes (SGOT, SGPT) (p>0.05). Conclusions: The risk factors of comorbidities, like diabetes, hypertension and others like leucocytosis, high CRP, high d-dimer, altered renal function, low serum albumin, and higher CT severity score could help clinicians identify patients with potential adverse events.